Error Analysis of Students’ Writing Composition at Vocational High School Context - Wahyu Prihanti, Adhila Nur'aini (RETAIN : Journal of Research in English Language Teaching, 2025)
Writing has been taught and learned as an essential skill for beginner learners to the advanced learner. Definitely, writing becomes regular lesson skill to practice, either in school or university. However, even it is learned and practiced often, making error is inevitable in writing. Thus, this study present study aims to analyze the grammatical errors made by vocational high school students in writing narrative text writing. The participants of this study were tenth grade students of a vocational high school in Surabaya. This research was conducted qualitatively. The researcher instructed students to write a narrative composition texts, then the data is processed by identifying and categorizing some errors that found in students’ writing composition. The types of error are classified by surface structure taxonomy (Dulay, Burt, & Krashen, 1982). The result of the study showed that the students made errors in misformation, addition, and omission. The frequent error made by the students is misformation in using past tense.